Desarrollo de una aplicación para implementar un modelo predictivo de inyección química (2017)
It is presented an application developed in the Visual Basic programming language that allows to determine the behavior of oil fields, in which processes of waterflooding, polymer flooding, surfactant flooding and surfactant-polymer flooding are applied through an analytical model that considers the Buckley-Leverett theory and the streamtubes method. The application does not replace the numerical simulation because it does not consider the static model of the reservoir and, in general, it requires little input information. However, it is a quick approach of prediction that makes possible to obtain summary tables and graphs of oil and water production rates and cumulative production and oil recovery factor, besides comparing with results obtained from other type of predictive tools.